O conhecimento tradicional das populações rurais sobre a classificação e (trans) formação de paisagens das caatingas sob o olhar da etnoecologia da paisagem - Mota, Janay Clésia Menezes (Universidade Federal Rural do Semi-Árido, 2018)
The local ecological knowledge about the formation of landscapes is based on the cumulative set of observations, practices and beliefs that humans possess in relation to the environment in which they live. They act in the landscapes contributing to their modification through techniques acquired and apprehended from the systematization of their knowledge about the biotic and abiotic factors. In this way, the present dissertation aims to understand the perception of rural communities inserted in areas of the caatingas as to the formation, transformation and classification of the surrounding landscapes. The dissertation is structured in two chapters: the first deals with the criteria that the interviewees use to classify Caatingas’ landscapes, similarities and differences between traditional and academic classification systems while the second chapter addresses the understanding of the transformations that occurred in the Caatinga in the last five decades from the perspective of local knowledge and the use of satellite images. The selection of key informants was made through the "snowball" technique. An ethno-mapping was carried out in order to generate a cartographic sketch of the rural property and adjacent areas of each collaborator; and the technique of guided tour was applied in order to obtain the identification of the spaces (landscapes units) that were indicated by each interviewee when preparing the ethno-maps. Semi-structured interviews were conducted in each property visited to obtain information about the knowledge that each interviewee has in relation to the formation of the surrounding landscapes. In the second chapter, the technique of timeline and historical chart was carried out, as well as semi-structured interviews in order to obtain information about the transformations occurring in the surrounding landscapes. For the elaboration of thematic maps from the Remote Sensing, INPE (National Space Research Institute) images were selected for the years 1985, 2004 and 2017. The Landsat 5 satellites were used for the images referring to the years of 1985 and 2004, and for the year 2017, images from Landsat 8 were used, and bands 3 and 4 were used for each year. The images were georeferenced in the QGIS version 2.18.13 program and the Datum used was SIRGAS 2000. The vegetation dynamics analysis was performed using the NDVI index, where we obtained six reflectance intervals and five surface targets: areas without vegetation, herbaceous stratum, shrub-open stratum, shrub-arboreal stratum and arboreal-shrub stratum. The interviewees recognized 19 landscape units for the ecoregions sampled, and these were associated mainly with the categories related to relief, phytophysiognomies and anthropogenic origin. The identification and classification of the landscapes was based on multifactorial and multidimensional criteria, such as geomorphology, vertical and horizontal vegetation structure, soil types, vegetal taxonomy, popular toponyms and other characteristics of the ecotypes. Regarding the ethical / emic aspects of landscape classification we can infer that there are some similarities, such as the characteristics described for landscape classification related to physiognomic aspects, relief, soil types and dominant species, influencing how each knowledge system identifies, classifies and delimits the landscape units of the caatingas. The NDVI for the periods 1985, 2004 and 2017 showed a general tendency of vegetation replacement, being the classes 5 (shrub-arboreal) and 6 (arboreal-shrub) substituted by vegetation of class 4 (shrub-open) and class 3 (herbaceous). The comparison between the use of images and the local knowledge showed differences as congruences. In relation to the former, they are believed to be fundamentally related to the different scales used to collect data in each knowledge system. In addition, most of the image studies focus primarily on the patterns found at the expense of the processes involved. Local knowledge can contribute to a better connection between patterns and processes, since the sertanejos (at least locally) provided an excellent record of the productive activities of the several decades sampled, including the decades in which there were no images available for use.
Keywords: Folk; Sucessão florestal; Ecorregiões; NDVI; Semiarid; Folk; Forest succession; Ecoregions; NDVI; Semiárido; CIENCIAS BIOLOGICAS::ECOLOGIA